Effect of pig birth weight and castration age on growth performance, hematological and antioxidant parameters in suckling period - Safaie, Eva S; Kwon, Chan-Ho; Torres, Jannell A; Jang, Young-Dal (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Castration is one of the most stressful events for suckling pigs. Increasing castration age may help alleviate the stress associated with castration, with the effect depending on the pig’s birth weight. Objective: This study was conducted to investigate the effect of birth weight and castration age on growth performance, hematological and antioxidant parameters of suckling pigs. Methods: At birth, a total of 32 male pigs from 8 litters were assigned to castration age and birth weight. Treatments were: 1) d4-HBW: high-birth weight (HBW; ≥1.5 kg) pigs castrated on d 4 of age, 2) d9-HBW: HBW pigs castrated on d 9 of age, 3) d4-LBW: LBW (≤1.3 kg) pigs castrated on d 4 of age, and 4) d9-LBW: LBW pigs castrated on d 9 of age. Growth performance, hematological and antioxidant parameters were measured at weaning. Results: The HBW pigs had a greater ADG (p<0.05) than LBW pigs in the suckling period, while there was no difference between pigs castrated at d 4 and d 9 of age. With an interaction between birth weight and castration age (p<0.05), the d4-HBW pigs had a lower ADG in d 4 to 9 of age than d9-HBW pigs, while no difference was observed between d4-LBW and d9-LBW pigs. At weaning, d9-castration pigs had greater hemoglobin levels (p<0.05), but lower basophil percentage (p=0.07, tendency) and plasma malondialdehyde (p<0.05) levels than d4-castration pigs. The HBW pigs showed lower hemoglobin (p<0.05) and hematocrit (p=0.06, tendency) levels than the LBW pigs. Conclusion: The castration age did not affect the growth performance of pigs until weaning although early castration for the HBW pigs may temporarily slow their growth rate. Late castration resulted in greater hemoglobin levels and reduced oxidative stress compared to early castration. Despite growing faster than the LBW pigs, the HBW pigs had lower hemoglobin and hematocrit levels.